Discovery of a DFR gene that controls anthocyanin accumulation in the spiny Solanum group: roles of a natural promoter variant and alternative splicing. (18th July 2022) - Wang, Xing; Chen, Xueping; Luo, Shuangxia; Ma, Wei; Li, Na; Zhang, Weiwei; Tikunov, Yury; Xuan, Shuxin; Zhao, Jianjun; Wang, Yanhua; Zheng, Gengdi; Yu, Ping; et al.
SUMMARY: Anthocyanins are important pigments that impart color in plants. In Solanum, different species display various fruit or flower colors due to varying degrees of anthocyanin accumulation. Here we identified two anthocyanin‐free mutants from an ethylmethane sulfonate‐induced mutant library and naturally occurring mutants in Solanum melongena, with mutations in the 5′ splicing site of the second intron of dihydroflavonol‐4‐reductase ( DFR ) – leading to altered splicing. Further study revealed that alternative splicing of the second intron was closely related to anthocyanin accumulation in 17 accessions from three cultivated species: S. melongena, Solanum macrocarpon and Solanum aethiopicum, and their wild related species. Analysis of natural variations of DFR, using an expanded population including 282 accessions belonging to the spiny Solanum group, identified a single‐nucleotide polymorphism in the MYB recognition site in the promoter region, which causes differential expression of DFR and affects anthocyanin accumulation in fruits of the detected accessions. Our study suggests that, owing to years of domestication, the natural variation in the DFR promoter region and the alternative splicing of the DFR gene account for altered anthocyanin accumulation during spiny Solanum domestication. Significance Statement: Variations in the DFR promoter strongly affect anthocyanin biosynthesis, and alternative splicing of DFR contributes to the diversity of anthocyanin pigmentation during spiny Solanum group domestication.